Socially relevant philosophy of science: an introduction - Carla Fehr; Kathryn S. Plaisance (Synthese, 2010)
This paper is an argument for a more socially relevant philosophy of science (SRPOS).  Our aims in this paper are to characterize this body of work in philosophy of science (POS), to argue for its importance, and to demonstrate that there are significant opportunities for POS to engage with and support this type of research.  The impetus of this project was a keen sense of missed opportunities for POS to have a broader social impact.  We illustrate various ways in which POS can provide social benefits, as well as benefits to scientific practice and philosophy itself.  Also, SRPOS is consistent with some historical and contemporary goals of POS.  We’re calling for an expansion of POS to include more of this type of work.  In order to support this expansion, we characterize POS as an epistemic community and examine the culture and practices of POS that can help or hinder research in this area.